Analisis Peranan Pertanian Terhadap Perekonomian Kabupaten Samosir Provinsi Sumatera Utara - Nainggolan, Lamhot; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research was conducted in District Samosir and aimed to identify the role of the agricultural sector  in the regional economy and the likely changes the position of agricultural sector in the future. The research method usest in this study are Locationt Quotient Analysis, Dynamic Location Quotient, Coefficient of Localization and Specialization, Shift share Analysis And Growth Profile Analysis. This research use data of GDP from 2006-2010 and related data. The results showed that Agriculture sector is a base sector of the economy at district  Samosir. There are five sub-sectors of agriculture sector in Samosir regency food crops sub-sector , Plantation , Livestock, Forestry , Fisheries. Results Locationt Quotient ( LQ ) shows that the sub sector Livestock and Forestry is a sector basis . analysis while the analysis of the Location Quotient and Dynamic Location Quotient show that Agriculture sector is expected to change from base sector tobe non base in the future. Localization coefficient indicates that agricultural activities carried out in the district are concentrated in Samosir and specialize in livestock and forestry sub-sectors . Shift share results indicate a positive shift in the economic structure in District Samosir. Agriculture sector growth profile describes indicate a slow growth and poor competitiveness compared with other regions in North Sumatera Utara Province. Keyword : Locationt Quotient Analysis, Dynamic Location Quotient, Shift share